2016
DOI: 10.1097/jcp.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Palmitate Once-Monthly Injectable Treatment for Acute Exacerbations of Schizoaffective Disorder

Abstract: Supplemental digital contents are available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Studies have revealed that paliperidone is effective in the treatment of schizoaffective disorder [ 49 , 50 ]. The once-monthly PLAI used to treat patients with acute exacerbation of schizoaffective disorder alleviated psychotic symptoms and manic and depressive symptoms [ 49 ]. Paliperidone has also been demonstrated to alleviate depressive symptoms in patients with schizophrenia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that paliperidone is effective in the treatment of schizoaffective disorder [ 49 , 50 ]. The once-monthly PLAI used to treat patients with acute exacerbation of schizoaffective disorder alleviated psychotic symptoms and manic and depressive symptoms [ 49 ]. Paliperidone has also been demonstrated to alleviate depressive symptoms in patients with schizophrenia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…47,[49][50][51]53,55 The only study reporting the advantage of PP1M on oral antipsychotics showed several limitations, the main being a suboptimal statistical power due to the small sample size and the inclusion in the study cohort of both new and old PP1M users. 54 The main causes of drug discontinuation before the planned study end were adverse events 45,46,61,62,65 and ineffectiveness. 47,51,59,62,65,66 The two available long-term studies on PPM3 showed a rate of premature discontinuation similar to that shown by the active comparator (PP1M).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the double-blind phase of the study by Fu et al, there were small differences in the discontinuation rate between patients randomized to PP1M and those receiving PLA. 45,46 The most common reasons for discontinuation in the active group were withdrawal of consent and onset of adverse events.…”
Section: Ari-lai and Ari-lxlmentioning
confidence: 99%
“…The injectable form seems to be safer than oral paliperidone, given that it has lower rates of spontaneously reported EPS, lower rates of antiparkinsonian medications use, and a more considerable improvement on EPS scales [2]. Nevertheless, EPS remain a common treatment-emergent adverse effect in patients receiving PP regardless of the injection's dosage, reaching an incidence of 8.5% in various open-label studies [9,10]. In a very recent 18-months cohort study, 31.3% of patients receiving the LAI PP developed EPS, akathisia (13.4%) and parkinsonism (16%) being the most common [11].…”
Section: Discussionmentioning
confidence: 99%